The Portuguese Royal Treasury: management, taxation and accounts control in the Johannine period (from 1814 to 1820) - Nascimento Pedroso, Claudio; Cosenza, José Paulo; Donoso-Anes, Alberto (De Computis, Revista Española de Historia de la Contabilidad., 2020)
In November 1807, Napoleon Bonaparte's troops were about to invade Portugal. To escape, the Queen of Portugal, Maria I, her son, future King Juan VI, Prince Regent at the time, as well as civilians and military men, had to embark and move to Brazil urgently. The transfer of the Portuguese court to Brazil transformed the then colony of Portugal into the seat of the Portuguese monarchy, giving the country a significant role in the economic, social, and political issues of the Portuguese Empire, between 1808 and 1821. Among the changes made by the Portuguese Crown in Brazil in the process of reorganization of the State apparatus, we highlight the creation of the Royal Treasury, similar to the one existing in Lisbon since 1761, which was responsible for the collection and accounting entries of the income generated throughout the Portuguese domain. This paper examines the balance sheets of the ledger book of the 2nd Royal Treasury General Accountancy from 1814 to 1820, based on historical and documentary research conducted in the collections of the Brazilian National Archive. The purpose of this study is to analyze the quality of the accounting information recorded in the annual balance sheets, comparing it across different periods and determining its functionality as a tax control tool. The paper contributes to the literature with information on this special historical period in which Rio de Janeiro provisionally became the capital of the Portuguese Kingdom, maintaining a vital role in the political, economic, and social context of the time. The results of the study enable us to infer the economic conception of fiscal control that the Royal Treasury exercised in its administrative and accounting organization, showing the role played by accounting in the management of the Portuguese Royal House, given that accounting records reveal the ascendancy of the environment over accounting and the influence of accounting on the environment.